Bimodal neuromodulation combining sound and tongue stimulation reduces tinnitus symptoms in a large randomized clinical study - Conlon, Brendan; Langguth, Berthold; Hamilton, Caroline; Hughes, Stephen; Meade, Emma; Connor, Ciara O; Schecklmann, Martin; Hall, Deborah A.; Vanneste, Sven; Leong, Sook Ling; Subramaniam, Thavakumar; D’Arcy, Shona; et al. (https://science.sciencemag.org/, 2020)
Tinnitus is a phantom auditory perception coded in the brain that can be bothersome or debilitating for 10-15% of the population. Currently, there is no clinically recommended drug or device treatment for this major health condition. Animal research has revealed that sound paired with electrical somatosensory stimulation can drive extensive plasticity within the brain for tinnitus treatment. To investigate this bimodal neuromodulation approach in humans, we evaluated a noninvasive device that delivers sound to the ears and electrical stimulation to the tongue in a randomized, double-blinded, exploratory study that enrolled 326 adult subjects with chronic subjective tinnitus. Participants were randomized into three parallel arms with different stimulation settings. Clinical outcomes were evaluated over a 12-week treatment period and a 12-month post-treatment phase. For the primary endpoints, participants achieved a statistically significant reduction in tinnitus symptom severity at the end of treatment based on two commonly used outcome measures, Tinnitus Handicap Inventory (Cohen’s d effect size: 0.87 to 0.92 across arms; p<0.001) and Tinnitus Functional Index (0.77 to 0.87; p<0.001). Therapeutic improvements continued for 12 months post-treatment for specific bimodal stimulation settings. Long-term benefits lasting 12 months have not previously been demonstrated in a large cohort for a tinnitus intervention. The treatment also achieved high compliance and satisfaction rates with no treatment-related serious adverse events. These positive therapeutic and long-term results motivate further clinical trials towards establishing bimodal neuromodulation as the first clinically recommended device treatment for tinnitus.